2013
DOI: 10.1002/hed.23333
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characteristics of incidental and nonincidental papillary thyroid microcarcinoma in 339 patients

Abstract: Our results indicate that a high rate of PTMC presented 1 or more risk factors including multifocality, bilaterality, capsule invasion, and lymph node metastasis. Therefore, we suggest total thyroidectomy followed by adequate exploration of the central neck compartment for possible nodal involvement and resection as a safe therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 24 publications
6
48
1
2
Order By: Relevance
“…NITMC, which presents with aggressive features like conventional TC, should be treated in a similar manner and a routine total thyroidectomy with central lymph node compartment dissection should be performed (35). Similar observations were noted in a study by Vasileiadis et al (36), which recorded 339 individuals with the papillary type of TMC, accounting for 12% of all patients who underwent surgery for thyroid disease. It was noted that bilaterality, autoimmune thyroid disease, a tumor size of >5 mm in diameter, multifocality and lymph node metastasis were significantly associated with non-incidental tumors.…”
Section: Tumor Size MM ---------------------------------------------supporting
confidence: 66%
“…NITMC, which presents with aggressive features like conventional TC, should be treated in a similar manner and a routine total thyroidectomy with central lymph node compartment dissection should be performed (35). Similar observations were noted in a study by Vasileiadis et al (36), which recorded 339 individuals with the papillary type of TMC, accounting for 12% of all patients who underwent surgery for thyroid disease. It was noted that bilaterality, autoimmune thyroid disease, a tumor size of >5 mm in diameter, multifocality and lymph node metastasis were significantly associated with non-incidental tumors.…”
Section: Tumor Size MM ---------------------------------------------supporting
confidence: 66%
“…The detection of multicentricity in thyroid cancer is important as it may affect treatment methods to be used. The studies in the literature report a multicentricity rate for papillary thyroid carcinoma ranging from 9.5% to 24.9%, and the rate of multricentricity was 38.9% in the present study (12,13). Pathological subtype is another factor affecting prognosis of papillary thyroid cancer.…”
Section: Discussionsupporting
confidence: 59%
“…Our 12.1% rate is comparable to rates from other European countries, including Belgium, Italy (25,30,33) and Greece (17). Because Italy and Greece have no nuclear plants, we tend to exclude that our rate was influenced by the relative vicinity of our medical center and residence of patients to three nuclear plant units (82).…”
Section: Discussionmentioning
confidence: 54%
“…, has shown that one-third (n = 16) of the studies are on cohorts of thyroidectomized patients smaller than ours (n = 50 to 191, compared to 207), and oneseventh of the studies (n = 7) are on cohorts slightly greater than ours (256 to 8,132). Prevalence of ITC at surgery ranges between 2% and 40% (1,2,17,. In Europe, the frequency of ITC varies from 2.2% to 27.4%, and a similar wide range (3.3% to 33%) is observed in the United States.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation